Rhein-Main Air Base, Germany (Special Collections, Gettysburg College, 2014)
Caption: General Dwight D. Eisenhower, chief of Allied Forces in Europe, hastens to greet members of Ohio's 433rd Troop Carrier Wing at today's ceremonies welcoming them as the first U.S. Air Force unit to join the North Atlantic Pact Organization under his command. With Gen. Eisenhower from left to right are; Col Harry W. Hopp, Commanding officer of the Wing, Maj Gen Dean C. Strother, Commanding General 12th Air Force, and Col A. C. Strickland, Commanding officer of Rein-Main Air Base.